2008
DOI: 10.1016/j.orggeochem.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotope fractionation during aerobic biodegradation of n-alkanes and aromatic compounds in unsaturated sand

Abstract: Microcosm experiments were conducted to quantify carbon isotope fractionation during aerobic biodegradation of n-alkanes (from C 3 to C 10 ) and monoaromatic hydrocarbons in unsaturated alluvial sand. In single compound experiments with n-alkanes, the largest enrichment factor was obtained for propane (À10.8 ± 0.7‰). The magnitude of the enrichment factor decreased with increasing number of carbon atoms from propane to n-decane (À0.2 ± 0.1‰). This trend can partly be explained by the decreasing probability tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 59 publications
4
27
0
Order By: Relevance
“…ω = 0. . b From (Bouchard et al, 2008c), MCP and MCH from (Bouchard et al, 2005). c n-hexane, n-octane and toluene from .…”
Section: Initial Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…ω = 0. . b From (Bouchard et al, 2008c), MCP and MCH from (Bouchard et al, 2005). c n-hexane, n-octane and toluene from .…”
Section: Initial Concentrationmentioning
confidence: 99%
“…Where α is the isotope fractionation factor for the compound of interest taken from (Bouchard et al, 2008c) and (Bouchard et al, 2005). For the column study, the biodegradation rate constant from the previous study was used as an initial value that requires adjustment as the biomass composition might have changed.…”
Section: Biodegradation Ratesmentioning
confidence: 99%
“…Table 4 lists the carbon isotope enrichment factors of the LMWHs considered here and in previous studies, along with values calculated using Eq. (5) (Craig 1953;Cerling et al 1991;Bouchard et al 2008c;Jeannottat and Hunkeler 2012). All the experimental values of e (e e ) for the C 6 -C 9 LMWHs are negative, indicating the enrichment of 13 C in the residual liquids and ''normal isotope fractionation'' during vaporization.…”
Section: Possible Mechanism Of Carbon Isotope Fractionation Of Lmwhs mentioning
confidence: 95%
“…The theoretical fractionation factor between the diffusion coefficients is given by the following equation (Craig 1953;Cerling et al 1991;Bouchard et al 2008c;Jeannottat and Hunkeler 2012):…”
Section: Quantification Of Isotope Fractionation During Vaporization mentioning
confidence: 99%
“…In addition, Strapoc et al (2007) found kinetic isotope fractionation in propane presumably produced through anaerobic microbial consumption. The kinetic isotope fractionation during aerobic microbial consumption of C 2 -C 4 hydrocarbons has been quantified in laboratory incubation experiments as well (Kinnaman et al, 2007;Bouchard et al, 2008). Thus, microbial consumption of C 3 (significantly), C 4 (moderately), and C 2 (partly) in thermogenic hydrocarbons could explain the observed molecular and isotopic fractionations of hydrocarbons.…”
Section: Initial Generation Of Hydrocarbons In the Bubblesmentioning
confidence: 99%